2010
DOI: 10.1007/s11427-010-0092-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis and breeding application of clonal diversity and dual reproduction modes in polyploid Carassius auratus gibelio

Abstract: A unisexual species is generally associated with polyploidy, and reproduced by a unisexual reproduction mode, such as gynogenesis, hybridogenesis or parthenogenesis. Compared with other unisexual and polyploid species, gibel carp (Carassius auratus gibelio) has a higher ploidy level of hexaploid. It has undergone several successive rounds of genome polyploidy, and experienced an additional, more recent genome duplication event. More significantly, the dual reproduction modes, including gynogenesis and sexual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
242
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 219 publications
(250 citation statements)
references
References 75 publications
4
242
0
4
Order By: Relevance
“…(Vasil'ev et al, 2003), Misgurnus anguillicaudatus (Itono et al, 2006), and their fertile function was revealed in unisexual Squalius alburnoides (Sousa-Santos et al, 2007) and Poecilia formosa (Lamatsch et al, 2010). In the triploid form of Carassius auratus complex, approximate 1-10% of triploid males were sporadically reported in natural habitats (Gui and Zhou, 2010), but the unusually triploid male incidence of high up to 23% should be firstly discovered in the gynogenetic triploid form. What are the reasons for the existence and high incidence of triploid males in the triploid form of Carassius auratus complex?…”
Section: Unusually High Incidence and Evolutionary Origin Of Triploidmentioning
confidence: 99%
See 4 more Smart Citations
“…(Vasil'ev et al, 2003), Misgurnus anguillicaudatus (Itono et al, 2006), and their fertile function was revealed in unisexual Squalius alburnoides (Sousa-Santos et al, 2007) and Poecilia formosa (Lamatsch et al, 2010). In the triploid form of Carassius auratus complex, approximate 1-10% of triploid males were sporadically reported in natural habitats (Gui and Zhou, 2010), but the unusually triploid male incidence of high up to 23% should be firstly discovered in the gynogenetic triploid form. What are the reasons for the existence and high incidence of triploid males in the triploid form of Carassius auratus complex?…”
Section: Unusually High Incidence and Evolutionary Origin Of Triploidmentioning
confidence: 99%
“…In the past, genetic evidence of sexual reproduction in triploid males has been demonstrated by experimental propagation and genetic marker analysis under captive condition (Gui and Zhou, 2010), but their ecologically genetic roles have remained unknown in natural habitats. In the present study, we utilized the existence difference of a relatively ubiquitous mtDNA CR2 haplotype in triploid females and triploid males to analyze the proportional relationship of triploids and triploid males with this haplotype in the four surveyed populations, and revealed the genetic evidence that sexual reproduction between triploid males and triploid females might have been performed in natural triploid form of the northeast Asia Carassius auratus complex.…”
Section: Evolutionary and Ecological Roles Of Triploid Malesmentioning
confidence: 99%
See 3 more Smart Citations